Thoracic and lumbar vertebrae of African hominids ancient and recent: morphological and fuctional aspects with special reference to upright posture - Benade, Maria Magdalena (My University, 2016)
This is a study of the morphological and functional aspects of A. africanus thoracic and lumbar vertebrae in comparison with those of modern human and anthropoid ape vertebrae. The purpose is to determine if any derived features in the morphology of hominids, as distinct from primitive features shared with non-hominids, were present and if so to what stage of attainment of full erectness such features point. The major results of this study are as follows: (i) There is a difference in the configuration of the lumbar articular facets between pongids, on the one hand, and modern human and A. africanus, on the other hand. This difference suggests that similar stresses operate in these regions in the two hominid groups. (ii) Bony adaptation to a developed lumbar lordosis is present in A. africanus. (iii) Major agreement has been found in the relative dimensions of modern human and A. africanus lumbar vertebrae, in contrast to those of pongid vertebrae. This indicates probable correspondence in the pattern of weight transmission to the pelvis in modern humans and A. africanus. (iv) The decrease of inferior lumbar vertebral body area starts at higher levels in sts 14 (an A. africanus partial skeleton) than in modern man, suggesting a longer curved lower lumbar region in A. africanus. From these results it may be concluded that the trunk was probably carried in a fully erect posture in A. africanus. The bony adaptation thereto, however, may not have been fully developed as in modern man. It is proposed that, in Sts 14, the last two lumbar vertebrae were carried at an angle relative to each other and to the sacrum, in contrast to the abrupt change in direction between L5 and the sacrum in modern man.
A Dissertation Submitted to the Faculty of Science University of the Witwatersrand, Johannesburg for the Degree of Master of Science January, 1990
Keywords: Australopithecines.; Lumbar vertebrae.; Thoracic vertebrae.; Fossil hominids -- Africa.